Correction to: Nursing competence in municipal in-patient acute care in Norway: a cross-sectional study - Torunn Kitty Vatnøy; Marianne Sundlisæter Skinner; Tor-Ivar Karlsen; Bjørg Dale (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.